Oxidation stress and antioxidant levels in tangerine pericarp - Yeung, P.M.Y.; Li, W.; Ip, et al., C.H. (Progress in Nutrition, 2011)
Summary Tangerine peel is a common traditional Chinese medicine and an herb for Chinese food preparation. In order to study the influence of oxidative stress, ozonated water, gaseous ozone and UV radiation were applied to potted tangerine plants and the antioxidant levels in fruit pericarp were compared. After being watered daily with 500 mL ozonated water (0.84 mg/L dissolved ozone) for two weeks; a 19.5% increase in pericarp antioxidant level was detected. After plant samples were exposed to 6 ppm ozone, 2.88 KJ/m2 UV or a combination of both for 30, 60 and 120 min daily for the same period; decreases in antioxidant level were found and were generally in proportion to the time course of treatment. The results indicated that the oxidants depleted the antioxidant in the pericarp of mature tangerine. Ozonated water application to soil, however, as a systemic response increased the antioxidant level in the pericarp. Stress ossidativo e livelli di antiossidanti nel pericarpo del mandarino tangerino Riassunto La buccia del mandarino tangerino è un ingrediente comune nella medicina tradizionale cinese e nella preparazione del cibo cinese. Al fine di studiare l’influenza dello stress ossidativo, le piante in vaso sono state sottoposte ad acqua ozonizzata, ozono gassoso e radiazioni UV e sono stati confrontati i livelli di antiossidanti nel pericarpo del frutto. Dopo essere state innaffiate giornalmente con 500 ml di acqua ozonizzata (0,84 mg/L di ozono dissolto) per 2 settimane è stato rilevato un aumento dei livello di antiossidanti nel pericarpo del 19,5%. In seguito campioni di piante sono stati esposti a 6 ppm di ozono, 2,88 KJ/m2 di UV o una combinazione di entrambi per 30, 60 e 120 minuti al giorno per lo stesso periodo; è stata riscontrata una diminuzione del livello di antiossidanti ed era generalmente in proporzione alla durata di trattamento. I risultati hanno indicato che gli ossidanti impoveriscono gli antiossidanti nel pericarpo del mandarino tangerino maturo. L’applicazione di acqua ozonizzata nel suolo, tuttavia, come una risposta sistemica aumentava il livello di antiossidanti nel pericarpo.